2020
DOI: 10.11646/zootaxa.4885.3.6
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Sphaerotheca Günther, 1859 (Anura: Dicroglossidae) from the degraded urban ecosystems of Bengaluru, Deccan Plateau, India

Abstract: The dicroglossid genus Sphaerotheca was erected by Günther in 1859, with its range of distribution in South Asia. Since then, 13 species have been described and 10 species are considered valid. Many of these descriptions were from low to mid-elevation ranges of homestead areas, agroecosystems and degraded landscapes with a few from forested areas. In the present account, a new species of Sphaerotheca, a genetically distinct lineage with a morphological character set distinguishable from its congeners, is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 891 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Calling frogs have evolved patterns of vocalization that reduce the risk of overlapping acoustic signals (Klump and Gerhardt 1992), and we have observed neighboring male S. maskeyi adjust the timing of their calls with respect to each other. Deepak et al (2020a) demonstrated considerable variation in this species across its extensive distribution, indicating that species-level identification could be difficult without handling frogs. The description of the call of S. maskeyi (as S. pashchima) by Prasad et al (2020) from the Penna Tiger Reserve, Madhya Pradesh, matches the type-A call described herein, suggesting that this call could be a good character for identifying S. maskeyi.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Calling frogs have evolved patterns of vocalization that reduce the risk of overlapping acoustic signals (Klump and Gerhardt 1992), and we have observed neighboring male S. maskeyi adjust the timing of their calls with respect to each other. Deepak et al (2020a) demonstrated considerable variation in this species across its extensive distribution, indicating that species-level identification could be difficult without handling frogs. The description of the call of S. maskeyi (as S. pashchima) by Prasad et al (2020) from the Penna Tiger Reserve, Madhya Pradesh, matches the type-A call described herein, suggesting that this call could be a good character for identifying S. maskeyi.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Of these six, Sphaerotheca appears least like the others in its spadefoot toad habitus. Yet subsequent molecular studies (e.g.,Kotaki et al, 2010; Hasan et al, 2014;Sanchez et al, 2018) consistently showed Sphaerotheca to be the sister of the "Fejervarya" lineage Deepak et al (2020). examined the relationships within the Indian subcontinent Sphaerotheca and showed that the Burmese species differed genetically from all In dian species and that S. breviceps, the name commonly applied to a southeastern Indian species, is not correct for the Burmese…”
mentioning
confidence: 99%
“…Globally, the Burrowing Frog genus, Sphaerotheca Günther, 1859, is represented currently by eight recognized species: S. bengaluru Deepak, Dinesh, Ohler, Shanker, Channakeshavamurthy, andAshadevi, 2020, S. breviceps (Schneider 1799). S. dobsonii (Boulenger 1882), S. leucorhynchus (Rao 1937), S. maskeyi (Schleich and Anders 1998), S. pluvialis (Jerdon 1853), S. rolandae (Dubois 1983), and S. strachani (Murray 1884) with their distribution in Pakistan, India, Nepal, Sri Lanka, Myanmar and Bangladesh (Frost, 2021).…”
mentioning
confidence: 99%